1996
DOI: 10.1212/wnl.46.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Isolated infarcts of the pons

Abstract: We studied 36 patients with MRI-proven isolated acute pontine infarct. Corresponding to the constant territories of intrinsic pontine vessels, infarcts followed a predictable distribution, enabling us to delineate three main syndromes. Twenty-one patients had a ventral pontine infarct. Motor involvement varied from mild hemiparesis (ventrolateral pontine syndrome) to severe hemiparesis with bilateral ataxia and dysarthria (ventromedial pontine syndrome). In addition, three-fourths of the patients had clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
152
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(173 citation statements)
references
References 30 publications
(3 reference statements)
18
152
0
3
Order By: Relevance
“…10,11 However, with the development of neuroimaging such as CT and MRI, large artery atherosclerosis (eg, BA stenosis) or cardiac thrombus have been identified as rare causes of pontine SDPI. 12 In our study, we showed that basilar atherosclerotic plaque could be in fact much more frequent in SDPI than previously thought. Our results were different from Fisher's pathological observation.…”
Section: Discussionsupporting
confidence: 51%
“…10,11 However, with the development of neuroimaging such as CT and MRI, large artery atherosclerosis (eg, BA stenosis) or cardiac thrombus have been identified as rare causes of pontine SDPI. 12 In our study, we showed that basilar atherosclerotic plaque could be in fact much more frequent in SDPI than previously thought. Our results were different from Fisher's pathological observation.…”
Section: Discussionsupporting
confidence: 51%
“…A mRS score of 6 was used for patients who died during the study period. Patients with FmRS ≤2 were considered to have a good outcome; patients with FmRS > 2 were considered to have a bad outcome (Bassetti et al., 1996) in PPD. Six months after stroke is the period for most functional recovery and is considered to be appropriate for assessing the outcome (Duncan, Jorgensen, & Wade, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…7,11 Unilateral pontine infarctions usually manifest with lacunar syndromes, including pure motor stroke, ataxic hemiparesis, or dysarthria-clumsy hand. [12][13][14] Progression of motor weakness is relatively common in acute pontine infarction cases and is frequently associated with increased functional disability. 1 Recently, basilar artery (BA) stenosis was reported to be related to the subacute increase in lesion volume seen in pontine infarctions but was not correlated with clinical outcomes.…”
mentioning
confidence: 99%